Solar urticaria - Wolska, Hanna; Wolf-Makowska, Anna; Misiak-Gałązka, Magdalena (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction . Solar urticaria (SU) is a rare photodermatosis induced by a broad spectrum of electromagnetic radiation. Theoretically it should not present a diagnostic problem, but in everyday practice it is quite frequently misdiagnosed. Objective . To characterize SU cases diagnosed in the photobiology unit of the Dermatological Department of WUM, with particular analysis of conformity of initial diagnosis with that established in the photobiology unit. Material and methods. Investigation was performed in 87 patients directed to the photobiology unit with diagnosis of solar urticaria (out of 12 041 patients with different forms of light hypersensitivity tested). In all patients in order to determine sensitivity to UVB and UVA phototests were performed. They included evaluation of minimal urticarial dose. As the light source fluorescent bulbs emitting a continuous spectrum of UVB or UVA were used. In 5 patients to evaluate sensitivity to visible light a slide projector was used. In 30 patients additionally photopatch tests were done. Results . Our results confirmed rare occurrence of solar urticaria. Diagnosis of US was confirmed only in 15 out of 87 patients with such initial diagnosis (17.2%); they represented 0.12% of all patients with photodermatoses tested. In this group there were 8 women and 7 men of mean age 26.2 years (M), 25.7 years (W). In the majority (9) of cases the disease lasted one year before testing. The US action spectrum in our patients was UVA + UVB in 9 cases, mainly UVA in 2, mainly UVB in 2, and in two patients urticarial wheals were provoked by UVA, UVB and visible light. We did not notice either delayed onset or prolonged duration of urticaria. Photopatch testing and longer (up to 2 weeks after UV exposure) observation of irradiated sites enabled us to make a proper diagnosis in further 52 patients. In 35 we disclosed polymorphic light eruptions, in 12 contact dermatitis to chromium, in 2 photocontact dermatitis to chlorpromazine and fragrance substances. In 3 patients we diagnosed chronic actinic dermatitis. In 20 cases it was not possible to establish a definite diagnosis. Wrong initial diagnosis was observed mainly in patients hypersensitive to UVA. Conclusions . In patients with oedemato-erythematous lesions after sun exposure lasting longer than 24 h, particularly in the elderly, diagnostic procedures should include additionally to phototesting patch and photopatch tests.